DETERMINATION OF BOOK LOAN ASSOCIATION PATTERN USING APRIORI ALGORITHM IN PUBLIC LIBRARIES - Irfiani, Eni (Jurnal Techno Nusa Mandiri, 2020)
One way to increase knowledge is by reading literature from books. The young generation as the nation’s hope generation is expected to have a high interest in reading to broaden their horizons. Libraries as a place for literature books to provide various types of books. The use of books available in the public libraries of Depok city is still insufficient as seen from the low number of books borrowed by members, especially among the younger generation aged 17 to 25 years. Therefore it is necessary to have a pattern to see the books that are often borrowed by members so that the supply of the types of books that are most attractive to the younger generation that is provided becomes more varied. The method used to determine the association pattern of lending books to the library is using a priori algorithm. From the research results, there are seven rule associations with books that have the highest confidence value and are most often borrowed simultaneously, namely history books and novels as well as history and philosophy. Based on rule association, it is able to assist library officers in providing the most popular types of books among adolescents. In addition, the research results can be used as a reference in placing the book layout on the shelf based on the books that are most often borrowed simultaneously.